ANALISIS POLA DISTRIBUSI USAHA TELUR IKAN TERBANG DI KECAMATAN GALESONG KABUPATEN TAKALAR - HERDIANA HERDIANA (GANEC SWARA, 2019)
This study aims to (1) Identify the distribution patterns of flying fish eggs in Takalar District, (2) Analyze the profit and marketing margins of flying fish egg marketing institutions, (3) Analyze and identify distribution problems in the flying fish egg marketing agency.     This research was conducted in the village of Palalakan, Galesong District, Takalar District. Data was collected through observation and structured and in-depth interviews with the samples selected by purposive sampling on 43 respondents consisting of 30 patriotic fishermen, 10 Papalele, 2 collecting traders and 1 exporter using qualitative and quantitative descriptive analysis (margin formula, profit) and Fishbone analysis.     The results of the study show that (1) The distribution pattern of flying fish eggs is one-way in accordance with co-workers where fishermen market to papalele, papalele to collectors, and collector traders to exporters (2) Exporters have greater margins and profits than other institutions which are Rp.50,000 per kilogram, (3) The results of the fishbon analysis show that the distribution pattern of flying fish eggs shows that patoranist fishermen are people who do not have big profits because they do not have full power in determining prices due to the inability of fishermen to finance their own business capital loans from other institutions especially to papalele, so there needs to be a change in the pattern of distribution and the involvement of the government to help patoranist fishermen so they can have their own capital so that they do not depend on other business institutions